Frequency of Pregnancy Induced Hypertension in Patients Admitted in Maternity Ward of Ayub Medical Teaching Hospital Abbottabad - Raza, Sajid; Adnan, Muhammad; Ullah, Faqir; Khan, Nasir; Anwer, Rubia; Awan, Muhammad Taha; Khan, Azhar Abbas (Indus Journal of Bioscience Research, 2025)
Background: Hypertension is one of the most common medical disorders associated with pregnancy. It is the second leading cause of maternal mortality during pregnancy and affects one pregnancy in every ten cases. Maternal and fetal complications associated with hypertension can be highly destructive and can lead for example stroke, seizures, placental abruption, fetal death, and maternal death etc. In the current study, we tend to provide a comprehensive but short review of literature relevant to pregnancy induced hypertension. Importantly, its prevalence and distribution in Pakistan in general and in Abbottabad, Khyber Pakhtunkhwa, Pakistan in particular is discussed. In first section, however, a brief introduction and classification of pregnancy induced hypertension is addressed. Results: Total number of individuals are 125. Of these minimum ages of patients was 18 years and maximum were 45. Frequency of Pregnancy induced hypertension individuals were 57(45.60%) out of 125 patients and 68(54.40%) patients were without Pregnancy induced hypertension. 35(28%) patients were with history of pregnancy induced hypertension in previous pregnancy while 90(72%) did not have any history of PIH in previous pregnancy.33 (26.40%) of were doing regular exercise while 92(73.60%) had a sedentary lifestyle. 25(20%) had history of chronic hypertension while 100(80%) did not have any history of chronic hypertension. Conclusion: Effective operation of channel like improvement in general health of reproductive age females, health awareness of public, necessary antenatal care, prenatal diagnosis, optimal peripartum care, essential new born care program implementation and improving contraceptive prevalence are needed to lower perinatal mortality. This can be achieved through improving literacy rate, socioeconomic status and provision of free health facilities. Hypertensive disorders of pregnancy are an important cause of maternal and perinatal mortality and morbidity. Concrete steps should be taken so as to diagnose and manage hypertensive disorders during pregnancy to avoid the lethal morbidities.